2002
DOI: 10.1111/j.1527-2001.2002.tb00944.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Counseling and the Disabled: Feminism Examines the Stance of Those Who Stand at the Gate

Abstract: This essay examines the possible systematic bias against the disabled in the structure and practice of genetic counseling. Finding that the profession's "nondirective" imperative remains problematic, the authors recommend that methodology developed by feminist standpoint epistemology be used to incorporate the perspective of disabled individuals in genetic counselors' education and practice, thereby reforming society's view of the disabled and preventing possible negative effects of genetic counseling on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…In addition to reaching agreement on optimal content for discussions, disability advocates have also suggested that exposure to individuals with disabilities outside of a medical setting is an effective way of building comfort in discussing disability and facilitating informed decision-making [Saxton, 1996;Patterson and Satz, 2002;Brasington, 2007;Shakespeare et al, 2009]. They further argue that this approach has the effect of tempering beliefs engendered by the traditional medical model and encourages the development of a more nuanced view of disability [Saxton, 1996;Patterson and Satz, 2002;Brasington, 2007;Hodgson and Weil, 2012b].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition to reaching agreement on optimal content for discussions, disability advocates have also suggested that exposure to individuals with disabilities outside of a medical setting is an effective way of building comfort in discussing disability and facilitating informed decision-making [Saxton, 1996;Patterson and Satz, 2002;Brasington, 2007;Shakespeare et al, 2009]. They further argue that this approach has the effect of tempering beliefs engendered by the traditional medical model and encourages the development of a more nuanced view of disability [Saxton, 1996;Patterson and Satz, 2002;Brasington, 2007;Hodgson and Weil, 2012b].…”
Section: Discussionmentioning
confidence: 96%
“…They further argue that this approach has the effect of tempering beliefs engendered by the traditional medical model and encourages the development of a more nuanced view of disability [Saxton, 1996;Patterson and Satz, 2002;Brasington, 2007;Hodgson and Weil, 2012b]. Shakespeare et al also argue that, "perhaps the most dramatic learning can come when it is a peer who is disabled, rather than a patient" and advocate adjusting admissions procedures so that "suitably qualified people with disabilities can become health professionals.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In many obvious ways, the category of citizenship has been subjected to shifts in biological science and biotechnology, fields that directly attempt to understand and control life processes, including the coming into being of ongoing racist, eugenic, and genetic projects (including embryo selection, euthanasia debates, the Human Genome Project, genetic counseling, etc.) that actively aim to demarcate the healthy, competent, and desirable citizen (Dowbiggin, 1997;Ekberg, 2007;Gould, 1996;Kevles, 1995;Lemke, 2002;Patterson & Satz, 2002;Raz, 2009;Wendel-Hummell & Craig, 2009). This intersection between citizenship and the biological gives rise to the phenomenon of the biocitizen, or one whose citizenship is constituted as and through the biological (Rose & Novas, 2003).…”
Section: Death and The Living Statementioning
confidence: 99%
“…The case depicts how hard it is for counsellors to step aside and start thinking in a way that is different from their usual way of thinking, and how the model of non-directiveness in actually problematic in practice. Counsellors regularly present only negative images of disability in initial prenatal counselling sessions, which present a "constructed reality grounded in the scientific and medical definition of Unauthenticated Download Date | 5/13/18 4:27 AM a given genetic condition" (Patterson and Satz, 2005). Consequently, this necessarily significantly influences the decision of counselees.…”
Section: Ethical Dilemmas In Reproduction Counsellingmentioning
confidence: 99%